Eigenvalues of regular fourth‐order Sturm–Liouville problems with transmission conditions. (14th November 2016) - Li, Kun; Sun, Jiong; Hao, Xiaoling
Abstract : In this paper, a class of fourth‐order Sturm‐Liouville problems with transmission conditions is considered. The eigenvalues depend not only continuously but also smoothly on the problem. An expression for the derivative of the eigenvalues with respect to a given parameter: an endpoint, a boundary condition, a transmission condition, a coefficient, or the weight function, is found. Copyright © 2016 John Wiley & Sons, Ltd.